2019
DOI: 10.1007/s11033-019-04764-0
|View full text |Cite|
|
Sign up to set email alerts
|

TNF-α G-308A genetic variants, serum CRP-hs concentration and DNA damage in obese women

Abstract: Obesity is associated with inflammation, which can disturb genome stability. Tumor necrosis factor (TNF-α) polymorphism was found to affect TNF-α protein production and inflammation. Therefore, the present study illustrates the relationship between TNF-α polymorphism, the degree of inflammation assessed by serum high sensitivity C-reactive protein concentration (CRP-hs) and basal DNA damage in patients with obesity (BMI 30-34.9 kg/m 2) and control subjects with proper body mass (BMI < 25 kg/m 2). A total of 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…Consequently, we can reasonably suspect that the low expression of ZFP90 promotes the production of pro-inflammatory factors leading to the onset of arthritis. Besides, some studies have shown that pro-inflammatory factors can stimulate the production of CRP ( 36 , 37 ). Hence, in this study, SLE cases with a lower ZFP90 mRNA expression level had an elevated CRP level.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we can reasonably suspect that the low expression of ZFP90 promotes the production of pro-inflammatory factors leading to the onset of arthritis. Besides, some studies have shown that pro-inflammatory factors can stimulate the production of CRP ( 36 , 37 ). Hence, in this study, SLE cases with a lower ZFP90 mRNA expression level had an elevated CRP level.…”
Section: Discussionmentioning
confidence: 99%
“… 11 In obese individuals, numerous inflammatory mediators, like C reactive proteins, interleukin 6, and tumour necrosis factor-alpha are released by adipocytes. 12 All of these substances yield poorer health outcomes and mark obesity as a risk factor of cardiovascular complications; this may also be the cause of having higher prevalence in our study population.…”
Section: Discussionmentioning
confidence: 82%
“…b The IKBKE mRNA expression levels were suggestively higher (P = 0.021) in patients with CRP increased than those with CRP normal untoward death of the cell and accelerates the necrosis of the vessel wall. Some studies showed that TNF stimulates the production of CRP [23][24][25]. So it is reasonable to believe that the lack of IKKε promotes TNF signaling which leads to the elevation of CRP.…”
Section: Discussionmentioning
confidence: 99%